The risk of all-cause mortality, heart outcomes, cancer, and neurodegenerative disorders with cobalt-chrome-containing total hip arthroplasty implants: an analysis of the National Joint Registry. (1st March 2022) - Deere, Kevin; Matharu, Gulraj S.; Ben-Shlomo, Yoav; Wilkinson, J. Mark; Blom, Ashley W.; Sayers, Adrian; Whitehouse, Michael R.
Abstract : Aims: A recent report from France suggested an association between the use of cobalt-chrome femoral heads in total hip arthroplasties (THAs) and an increased risk of dilated cardiomyopathy and heart failure. Cobalt-chrome is a commonly used material in orthopaedic implants. If the reported association is causal, the consequences would be significant given the millions of joint replacements and other orthopaedic procedures in which cobalt-chrome is used annually. We examined whether cobalt-chrome-containing THAs were associated with an increased risk of all-cause mortality, heart outcomes, cancer, and neurodegenerative disorders in a large national database. Methods: Data from the National Joint Registry was linked to NHS English hospital inpatient episodes for 374, 359 primary THAs with up to 14.5 years follow-up. We excluded any patients with bilateral THAs, knee replacements, indications other than osteoarthritis, aged under 55 years, and diagnosis of one or more outcome of interest before THA. Implants were grouped as either containing cobalt-chrome or not containing cobalt-chrome. The association between implant construct and the risk of all-cause mortality and incident heart failure, cancer, and neurodegenerative disorders was examined. Results: There were 158, 677 individuals (42.4%) with an implant containing cobalt-chrome. There were 47, 963 deaths, 27, 332 heart outcomes, 35, 720 cancers, and 22, 025 neurodegenerative disorders. There was no evidence of an association that patients with cobalt-chrome implants had higher rates of any of the outcomes. Conclusion: Cobalt-chrome-containing THAs did not have an increased risk of all-cause mortality, or clinically meaningful heart outcomes, cancer or neurodegenerative disorders into the second decade post-implantation. Our findings will help reassure clinicians and the increasing number of patients receiving primary THA worldwide that the use of cobalt-chrome containing implants is not associated with significant adverse systemic effects.